Identification of critical heat stress zone for energy corrected milk yield in Murrah buffaloes using temperature humidity index under subtropical climatic conditions - BEHERA, RAJALAXMI; CHAKRAVARTY, A K; SAHU, ADHIKARI; KASHYAP, NEERAJ; RAI, SAROJ; DASH, SOUMYA; UPADHYAYA, ARPAN; SINGH, AVTAR; GUPTA, A K (The Indian Journal of Animal Sciences, 2018)
The present study was conducted to identify the critical heat stress zone (CHSZ) in a year for energy corrected milk yield (ECMY) of Murrah buffaloes. Monthly test day fat percentage data on 734 Murrah buffaloes spread over 20 years (March 1994 to 2013) were collected from ICAR-National Dairy Research Institute, Karnal and climatic parameters, viz. dry bulb temperature, wet bulb temperature and relative humidity for corresponding periods were collected from ICAR-CSSRI, Karnal. The overall least-squares means for monthly test day fat % ranged from 7.58±0.04 in TD2 to 8.02±0.04 in TD9. The monthly test day fat % data was adjusted for the significant non-genetic factors and was used to estimate ECMY (Kcal/kg). The non-heat stress zone (October–March) and heat stress zone (April–September) were identified based on the trend of monthly average test day ECMY in relation to monthly average THI. Within the heat stress zone, July to September exhibited maximum decline in the trait and was empirically identified as the CHSZ. Regression of monthly average ECMY (Kcal/kg) on monthly average THI in the empirically identified CHSZ was carried out to identify the most CHSZ. During July and August, maximum decrease (–8.18) in monthly average ECMY (Kcal/kg) was observed per unit rise in THI. Therefore, July and August months were identified as CHSZ for ECMY in Murrah buffaloes under subtropical climatic condition. Hence, heat stress amelioration programmes should be undertaken during the period to improve ECMY in Murrah buffaloes.